Analisis Kriminologi Mengenai Peredaran Narkoba Terkait dalam Keimigrasian - Abimanyu, Alief Akbar; Setia, Bangkit Bela; Soegiharto, Dwiki Bahtiar (Universitas Batanghari Jambi, 2024)
The circulation of narcotics has become an exceedingly complex and worrisome issue in the context of immigration-related crimes in Indonesia. This article presents a criminological analysis of the role of narcotics in immigration-related crimes with the aim of understanding their impact on national security and sovereignty. The literature analysis method was employed to gather and evaluate data related to this issue. The results reveal that the circulation of narcotics in immigration areas has serious repercussions on social stability and can be exploited by international networks for the purpose of drug trafficking. Tight monitoring at immigration checkpoints, rigorous law enforcement, and collaboration among agencies and internationally are pivotal in addressing this narcotics circulation. This article provides profound insights into the role of narcotics in immigration-related crimes and underscores the importance of collective efforts in combating this threat.